Russia Economic Report, No. 44, December 2020 : Russia's Economy Loses Momentum Amidst COVID-19 Resurgence; Awaits Relief from Vaccine - World Bank (World Bank, Washington, DC, 2020)
In Q2, Russia’s GDP contracted sharply, faced with domestic supply and demand, and terms of trade shocks. Yet supported by exports, GDP growth performed slightly above expectations. In the third quarter, as COVID-19 cases declined, restrictions eased and on the back of fiscal, monetary, and regulatory measures. Economic activity showed signs of picking up, as reflected by some resumption in industrial production sectors and services. However, negative momentum is expected to continue in Q4 amidst rising COVID-19 infection rates and re-installment of some mobility restrictions. The COVID-19 pandemic weakened corporate balance sheets, especially in services sectors such as hotels, tourist agencies, railway and airpassenger transportation.